Extraction of semi refined carrageenan from sabah seaweed using factorial analysis design expert - Muhammad Alif Farhan, Mohd Yusof (2024)
This study focuses on the extraction of semi-refined carrageenan from seaweed harvested in Sabah, Malaysia, utilizing factorial analysis design expert methodology. Carrageenan is a natural polysaccharide with various industrial applications due to its gelling, thickening, and stabilizing properties. There is a need to optimize the extraction process of carrageenan from seaweed to improve the quality and yield of carrageenan while minimizing the use of chemicals and reducing the environmental impact. The extraction process involves several factors, such as extraction temperature, potassium hydroxide concentration, and extraction time, which can significantly impact the yield and quality of carrageenan. Factorial analysis design expert is employed to optimize these extraction parameters and analyze their interactions to achieve the highest yield and quality of semi- refined carrageenan. The experimental results are analyzed using statistical tools to determine the optimal conditions for the extraction process. The findings of this study aim to contribute to the development of efficient and sustainable methods for the extraction of carrageenan from seaweed, with potential applications in the food, pharmaceutical, and other industries. The process parameters and the experimental design were conducted based on a two-level factorial design in Design Expert Software (DOE). This investigation started with collecting a sample of seaweed from Sabah. These samples were then extracted with varying conditions of potassium hydroxide concentration (6% and 12%), extraction time (1 and 3 hours), temperature (60 and 80 °C), and soaking time (0 and 14 days) using Design Expert. Subsequently, the samples were analyzed for significant responses such as yield and gel strength. Biodegradable packaging film was synthesized from 2% w/w plasticized SRC, supplemented with 0.9% natural plasticizer (glycerol), and enhanced with 10% cellulose nanofibers (CNF). Mechanical properties (tensile strength (TS) and elongation at break (EAB)) were investigated for the development of the biodegradable film.